Effect of Salt Concentrations for Fermentation Process on the Quality of Pla-som from Milkfish (𝘾𝙝𝙖𝙣𝙤𝙨 𝘾𝙝𝙖𝙣𝙤𝙨) - Klumklomjit, Sommarat; Dangkhaw, Nantida; Korsawaddipat, Prapat; Suksri, Chaweewan (Burapha Science Journal, 2026)
The fermentation of Pla-som using salt is a process for encouraging the growth of Halotolerant and Halophilic lactic acid bacteria and improvement of the texture and salty flavor of the product. The objective of this research was to study the effect of salt contents in the fermentation process on the quality of Pla-som from Milkfish. The experiment was performed using solid salt and brine at 10, 15, and 18%, respectively, then fermented in a vacuum bag at room temperature (30-35 °C) for 6 days. The results indicated that Pla-som prepared by using the solid salt formula showed the pH values of 4.38-4.57 and the salt contents of 1.5-2.09 g/100g, which were lower than that of Pla-som using the brine formula. However, their water activity contents (aw) (0.98-0.99) were higher than that of Pla-som using the brine formula (0.94-0.96). Very low contents of histamine in products were 8.46-30.99 mg/kg, while total viable count (TVC) was 1.2-2.0 x108 cfu/g and lactic acid bacteria (LAB) was 8.0 x107-1.7 x108 cfu/g, which were more than that of Pla-som using the brine formula. When the adding of salts increased, the amount of water activity, TVC, and LAB tened to decreases. The sensory evaluation from 30 panelists using the 9-point hedonic scale showed that the fried Pla-som products using 18% solid salt formula and 10% brine formula was no significant difference in overall acceptability scores (p>0.05). Pla-som prepared using 18% solid salt formula obtained the color, flavor, sour, taste, texture, and overall acceptability scores of 6.4, 6.6, 6.8, 7.3, 6.3 and 7.3, respectively. which was higher than the commercial product in all attibutes. Moreover, the pH of the product showed lower than 4.6, which was safe for consumption because high acidic conditions inhibited the growth of the most pathogenic bacteria. This suggests that the fermentation using 18% solid salt formula was suitable method for Pla-som production.